Detection of brain somatic variation in epilepsy‐associated developmental lesions. Issue 8 (23rd June 2022) - Bedrosian, Tracy A.; Miller, Katherine E.; Grischow, Olivia E.; Schieffer, Kathleen M.; LaHaye, Stephanie; Yoon, Hyojung; Miller, Anthony R.; Navarro, Jason; Westfall, Jesse; Leraas, Kristen; Choi, Samantha; Williamson, Rachel; et al.
Abstract: Objective: Epilepsy‐associated developmental lesions, including malformations of cortical development and low‐grade developmental tumors, represent a major cause of drug‐resistant seizures requiring surgical intervention in children. Brain‐restricted somatic mosaicism has been implicated in the genetic etiology of these lesions; however, many contributory genes remain unidentified. Methods: We enrolled 50 children who were undergoing epilepsy surgery into a translational research study. Resected tissue was divided for clinical neuropathologic evaluation and genomic analysis. We performed exome and RNA sequencing to identify somatic variation and we confirmed our findings using high‐depth targeted DNA sequencing. Results: We uncovered candidate disease‐causing somatic variation affecting 28 patients (56%), as well as candidate germline variants affecting 4 patients (8%). In agreement with previous studies, we identified somatic variation affecting solute carrier family 35 member A2 ( SLC35A2 ) and mechanistic target of rapamycin kinase ( MTOR ) pathway genes in patients with focal cortical dysplasia. Somatic gains of chromosome 1q were detected in 30% (3 of 10) of patients with Type I focal cortical dysplasia (FCD)s. Somatic variation in mitogen‐activated protein kinase ( MAPK) pathway genes (i.e., fibroblast growth factor receptor 1 [ FGFR1 ], FGFR2, B‐raf proto‐oncogene, serine/threonine kinase [ BRAF ], and KRAS proto‐oncogene, GTPase [ KRAS ]) was associated with low‐grade epilepsy‐associated developmental tumors. RNA sequencing enabled the detection of somatic structural variation that would have otherwise been missed, and which accounted for more than one‐half of epilepsy‐associated tumor diagnoses. Sampling across multiple anatomic regions revealed that somatic variant allele fractions vary widely within epileptogenic tissue. Finally, we identified putative disease‐causing variants in genes not yet associated with focal cortical dysplasia. Significance: These results further elucidate the genetic basis of structural brain abnormalities leading to focal epilepsy in children and point to new candidate disease genes.